Analisis Prospektif Strategi Pengelolaan Kawasan Gambut Secara Berkelanjutan Pasca Kebakaran di Kecamatan Bukit Batu Kabupaten Bengkalis - Dadang Mashur; Zaili Rusli; Zulkarnaini Zulkarnaini (Dinamika Lingkungan Indonesia, 2023)
Peat areas have unique characteristics as wetlands on land but are highly flammable if there are El Nino symptoms. The peat area has a protection function and a cultivation function and this is important for the life of living things. To date in 2021, where this research was conducted, the condition of the peat area in Bukit Batu District, Bengkalis Regency is very easy to burn, this requires a sustainable peat area management strategy from the ecological, social, and economic aspects so that fires do not occur in the future. This research can be useful for stakeholders to manage peat areas in a sustainable manner by taking into account the ecological, economic, and social aspects. Repeated fires in the same location make peat even more degraded. For this reason, it is necessary to manage post-fire peat areas, so a management strategy using prospective analysis is needed. The prospective analysis is a method that can be used to find strategies that can be applied in the future. The results of the prospective analysis in this study recommend that there are three strategies that need to be applied, from the ecological aspect, namely the conservation and rehabilitation strategy, from the social aspect, namely the MPA-preneurship strategy and from the economic aspect, namely the strategy of using burned land. These three strategies can be carried out simultaneously and holistically by involving many stakeholders in peat areas.